The Influence Of The Environment, Business Capital And Creativity Of Marketing Strategies In Increasing The Competitiveness Of MSMES In Bengkayang City - Blasius asis Blasius Manggu; Sabinus Beni Sabinus Beni; Silvester Sisil Silvester; Kusnanto Nanto Kusnanto (UNIVED Press, 2024)
One of the factors that encourages the development of MSMEs in Indonesia is support from the government. The government provides MSME actors with as much space as possible by following the rules contained in government regulations. The government's enormous attention to MSMEs is the right strategic step, in order to encourage the growth of our nation's economic development. The business environment can act as a creator of opportunities or as a threat. These opportunities or threats depend on the extent to which the power possessed can take advantage of existing opportunities. Business environmental factors consist of political, economic, social, cultural, educational, technological, demographic and legal. Having knowledge about the environment can encourage marketing creativity as an expansion of actions to market products. Creativity is centered on something new and meaningful from several outputs, towards general implementation in the field of marketing, and creativity requires the development of newer and more radical alternatives because it is a business solution effort faced by MSMEs every day. The innovation of an MSME is of course to adapt in a dynamic environment, MSMEs are required to be able to create new assessments, new ideas and offer innovative products. To run an MSME, capital is one of the important supporting factors that is absolutely necessary to run a business. Sources of capital can be obtained from own capital, government assistance, financial institutions, both banks and non-bank financial institutions. Every MSME that competes in an industrial environment has the desire to be superior to its competitors. MSMEs MSMEs that have competence in the fields of marketing, products, innovation can be used as a source to achieve competitive advantage. Competitive advantage can be interpreted as a benefit strategy from MSMEs collaborating to create competitive advantages, so that they can dominate in new markets and markets. The aim of this research is to find out whether there is an environmental influence on the competitiveness of MSMEs, whether capital factors can influence the competitiveness of MSMEs, whether marketing strategy creativity can influence the competitiveness of MSMEs. The first stage in this research is identifying problems, related to environmental warfare, business capital and MSME marketing creativity. The aim of the research is to identify aspects that are closely related to problems in the environment, marketing capital and creativity, literature study, literature review both journals and texts book, data processing, feasibility study regarding aspects of the role of the environment, capital and marketing creativity, analysis, extent of data processing results research, make conclusions, based on research results and make suggestions. The output of this research is articles published in accredited national journals. This type of research is descriptive quantitative, validity and reliability tests to measure concepts, classical assumption tests to test data so that it meets the Best Linear Unbiased Estimator (BLUE) criteria so that it can produce a valid estimator. KEYWORDS : Environment, Business Capital, Creativity, Marketing Strategy, MSMEs